Analysis of Tourism Strategic Area Development for Bali - Jaya, Martha; ., Sudarsana; Wiryasa, Anom (Journal of Civil Engineering, Architecture and Built Environment, 2020)
Master Plan of National Tourism Development (Rencana Induk Pengembangan Pariwisata Nasional - RiParNas: 20102025) determined by the President of the Republic of Indonesia on 2nd December 2011. National Tourism Strategic Area (Kawasan Strategis Pariwisata Nasional - KSPN) spread over 88 KSPN in 34 provinces throughout the territory of the Republic of Indonesia. Bali as the biggest foreign exchange contributor of the tourism sector has 11 KSPN spread in 9 districts and town in the province of Bali, namely: Buleleng district (area of Bali Utara-Singaraja, and Pulau Menjangan-Pemuteran); Jembrana (National Park of Bali Barat); Tabanan (Bedugul); Denpasar and Badung (Sanur-Kuta-Nusa Dua); Gianyar (Ubud); Bangli (Kintamani-Danau Batur); Klungkung (Nusa Penida); Karangasem (Besakih-Gunung Agung, Tulamben-Amed, and Labuhan Amuk). Development of Bali during this time indicated that there are still some gaps of development outcomes. The research objectives for the first year (2016) are: to identify, analyse and earlier understanding about Critical Factors (CFs) on developing tourism strategic area for Bali Provincial in supporting equitable economic developments. The data was collected using the method of observation and semi-structured interviews, while the Content Analysis Techniques (CAT) and Cognitive Mapping Solutions (CMS) are used as a method of qualitative-verification analysis. Thus, CFs can be identified into six categories called SLEEP'S, namely: Social-cultural, Legal-regulatory, Environment, Economic, Politic, and Safety. Therefore, the research can be conducted within three stages, in order to produce specific and maximum outputs.   Keywords : critical factors, cognitive mapping, content analysis, equitable economic development, tourism strategic area.